PENINGKATAN KEMAMPUAN PENGGUNAAN HURUF KAPITAL MELALUI STRATEGI LATIHAN (DRILL) PADA SISWA KELAS III SD - Karinna, Cahya; Najwa Azzahra, Nabilla; Khoyrul Ummah, Ullyl (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low ability of Grade III elementary school students to use capital letters correctly. The purpose of this study is to describe the application of the drill strategy and to analyze the improvement of students ability to use capital letters through this strategy. This study used the Classroom Action Research (CAR) method with the Kemmis and McTaggart model consisting of two cycles. The research subjects were 12 Grade III elementary school students. Data collection techniques included observation, tests, interviews, and documentation. Data analysis was conducted qualitatively and quantitatively. The results showed a significant improvement: in the pre-cycle, learning mastery only reached 33.3% with an average score of 62.5; in Cycle I it increased to 66.7% with an average of 78.3; and in Cycle II it reached 91.7% with an average of 85.0. Student learning activity also improved from the less active category to very good. Thus, the drill strategy is proven effective in improving the ability to use capital letters for Grade III elementary school students.